MRI Diagnosis of Patients Presenting with Low Back Pain: diagnosis of low backpain by using MRI - Maqsood, Mahnoor; Ali , Abid; Naeem , Muhammad Ahmad; Irram , Saadia; Mazhar , Mehlab; Ashraf , Nadia; Muzafar , Saba; Kalsoom , Ume (Medical Science Journal for Advance Research, 2023)
Background: The spine acts as a protective mechanism and houses and guards the vital and fragile spinal cord. MRI has the advantages of nonionizing radiation and excellent visual skills, especially for soft tissues. Objective: To utilize MRI to diagnose lumbar spine sufferers and determine what's causing their low back discomfort. Material and methodology: The study was a cross-sectional one conducted in a Sialkot, Pakistan, private hospital. A sample size of 83 was considered, and the convenient sampling method was used. Data were considered for six months, from October 2022 to March 2023, with informed consent and by the ethical standards outlined by the university's research council. A 0.35T Neusoft MRI scanner was used. Data were analysed using SPSS version 26. Results: In the current study, 69 (83.1%) were male and 14 (16.9%) were female. More men than women are impacted. The best method for identifying the causes of back pain is the sagittal and axial approach. The most effective method is sagittal and axial for confirming low back pain in around 76 (91.6%) individuals. In this study, 76 (91.6%) individuals had bulging discs. The most common patient complaint is lower back pain. Conclusion: An MRI is the most accurate way to diagnose lumbar-vertebral causes of back pain. The sagittal and axial approach is the most effective way to identify the causes of low backache. The most common patient complaint is lower back pain.